Investigating English Teacher Strategies for Slow Learners in Grammar Learning - Rizky Ummi Thahirah Nasution; Ahmad Amin Dalimunte (Universitas Islam Negeri Palopo, 2026)
Inclusive education aims to meet the needs of students from diverse backgrounds. Among them are slow learners, whose learning ability is lower than that of their peers. However, its implementation is still not optimal. Consequently, there is a risk that the learning needs of slow learners will not be met. One of the causes is the limited number of teachers, as well as their low level of readiness to face the diversity of students in inclusive classes. To overcome these limitations, teachers need to be aware of teaching strategies that can accommodate their needs. In particular, English teachers need to be aware of the strategies they use when teaching grammar, which is known to be important yet challenging for language learners. In fact, there are still a few studies that explore the use of teaching strategies for grammar for slow learners in inclusive classrooms. Therefore, this study aims to explore strategies for teaching grammar to slow learners and their implementation in inclusive classrooms. The qualitative study with a descriptive design involved English teachers and class teachers in grade 8 at a junior high school. Data was obtained through semi-structured interviews and field observations, and analyzed using thematic analysis. The results of the study show that teachers use structural, cooperative, translanguaging, and affective strategies, as well as repetition and visual media assistance, in grammar teaching. This study concludes that grammar teaching strategies not only focus on cognitive development, but also on approaches that promote the mental development and attitudes of slow learners.